Business and entrepreneurship in Saudi Arabia opportunities for partnering and investing in emerging businesses - Burton, Edward (John Wiley & Sons, Inc., 2016)
Drawing on his years of experience in counseling American business, in government as a diplomat living and working in Saudi Arabia, and as a businessman, Edward Burton introduces the reader to the emerging new class of entrepreneurs in the Kingdom of Saudi Arabia. The book answers the question why Saudi Arabia's current industrial and economic boom has relevance to global business and why it is important to American competitiveness to better know and understand Saudi Arabia. This book is important for investors also because of the following facts about Saudi Arabia.